Progress in Research of Dragon Rolled Plates. Issue 1 (August 2021) - Lei, Wu; Ming, Qin; Bing, He; Bin, Gu
Abstract: Progress in research of dragon rolled thick plates are summarized in this paper. Basic characteristics, reduction and gap supplement, plate bending, rolling force and energy parameters, shear deformation at the center of the thick plates and the materials and methods in current research were introduced. Although the potential of the application of dragon rolling in thick plate production is obvious, there are still many unsolved problems, especially that the experimental data is still less, therefore there is still a lot of work to do from the practical application.